A Derivative of s‐Triazine Modified Reduced Graphene Oxide with the Function of UV‐absorbing. Issue 1 (15th December 2015) - Liu, Tianye; Yan, Hongxia; Chen, Zhengyan; Xu, Peilun; Su, Shikun
Abstract: A new s‐triazine derivative modified graphene composite, in which 2, 4, 6‐tri(2, 4‐dihydroxyphenyl)‐1, 3, 5‐triazine (TDTA) was attached onto reduced graphene oxide (rGO) via the noncovalent functionalization approach, named TDTA/rGO, was reported. And the TDTA was synthesized via a Friedel‐Crafts reaction. FTIR and NMR spectroscopic characterizations were carried out to confirm the synthesis of TDTA. UV‐Vis, XPS and TEM revealed that TDTA molecules were successfully loaded onto graphene sheets by π‐π stacking, and the composite is found to improve greatly the dispersity of rGO in DMF and to be a good UV‐absorber. Abstract : TDTA/rGO, A new s‐triazine derivative modified graphene composite, in which 2, 4, 6‐tri(2, 4‐dihydroxyphenyl)‐1, 3, 5‐triazine (TDTA) was attached onto reduced graphene oxide (rGO) via the noncovalent functionalization approach, was reported. The composite is found to improve greatly the dispersity of rGO in DMF and to be a good UV‐absorber.